PWE-115 Patients Continue To Travel Abroad Despite Recently Active Disease And Travel Concerns: Results Of A Single Centre Study In Inflammatory Bowel Disease And Travel. (9th June 2014) - Shepherd, TC; Greveson, K; Mulligan, JP; Hamilton, MI; Murray, CD
Abstract : Introduction: Travellers with Inflammatory bowel disease (IBD) are at greater risk of travel-related morbidity. 1 Relapse and acquired infection are the main risks to IBD patients while abroad, and ECCO recommend expert consultation prior to travel, particularly for those on immunosuppression. 2 IBD limits a majority of patients choice of travel destination. 1 Despite this, there is limited data regarding IBD patients pre-travel preparation and travel experiences. Methods: Patients attending our IBD clinic during November 2013 were asked to complete an anonymous questionnaire. We asked for demographic and disease specific information, in addition to detailed travel questions; including perceptions, pre-travel planning and recent travel experiences. Data was entered and analysed on an anonymised database. We hypothesised that patients with travel concerns and those who had flared within the last 6 months would be less likely to go abroad in that same period. Results: A representative 136 IBD patients (67/136[49%] Crohn's disease, 60/136[44%] male, age 18–85 years [median age 38 years]) responded. 51%[69/136] were immunosuppressed and 43%[49/136] had IBD related surgery. 62%[84/136] experienced an IBD flare in the last 6 months. 60%[82/136] reported IBD affected travel. 58%[79/136] travelled in the last 6 months, despite a majority of those (65%[51/79]) reporting IBD affected travel. 59%[47/79] of travellers had experienced a flare in the last 6 months, although again, most of those (77%[36/47]) reported IBD affected travel. Only 18%[14/79] travellers (71%[10/14] had a recent flare) sought pre-travel medical advice of any kind and only 41%[32/79] (69%[22/32] had a recent flare) had travel insurance, the majority (88%[28/32]) paid a premium. 20%[16/79] travellers reported a change in bowel habit while abroad, but of those only 27%[3/11] sought medical advice. We also report that 52%[36/69] of immunosuppressed patients are unaware of the need to avoid live vaccines. Conclusion: A majority of IBD patients feel their disease affects travel. However, despite concerns, patients still travel abroad, even if they have suffered a recent flare. Our results suggest patients are not receiving the recommended travel medical advice, including the need to avoid live vaccinations if immunosuppressed, and are possibly under or not insured. The small numbers of travellers suffering a change in bowel habit abroad tend not to seek medical advice while away. Further detailed investigation in travel behaviour in IBD patients is required, but we suggest there is a need for greater IBD travel education. References: Soonawala D, et al . Inflamm Bowel Dis November 2012;18(11):2079–85 Rahier JF, et al . J Crohn Col February 2009 Disclosure of Interest: None Declared.